Devising an innovative method for improving decision-making efficiency at polymers processing companies in automotive industry - Prystynskyi, Serhii; Palyvoda, Olena; Plavan, Viktoriia; Lozovyi, Oleg; Hrytsenko, Andrii (Eastern-European Journal of Enterprise Technologies, 2024)
Enabling the development of technologies for the production of polymer materials directly determines the possibility of achieving the standards of sustainable development in the automotive industry, since polymer composites are used in modern cars as components of almost all assemblies and mechanisms. The expansion of plastics application in the car structure contributes to the reduction of fuel consumption and wear of parts. Technological changes encourage enterprises to constantly improve decision-making methods regarding the introduction of innovative technologies. This paper reports an innovative method devised for making management decisions at enterprises specializing in the processing of polymers for the automotive industry, which makes it possible to increase production efficiency. Based on the Ishikawa diagram and the PDCA cycle application, management tools and procedures for making production and technological decisions have been developed using the methodology of finding root causes and verifying factors influencing existing production problem. A set of indicators that make it possible to reduce the number of management errors has been substantiated; they increase the reliability of verifying received intermediate results of decisions. The selection of verification indicators was carried out taking into account the specificity of polymer production technologies. An improved decision-making management procedure is presented, which was embodied in an updated decision-tracking protocol. Unlike its basic version, it contains additional control points: target date of verification, date of verification, and result of verification. An experimental study showed that the application and observance of the full PDCA cycle increases the overall effectiveness of management by 63 %, which in turn has a positive effect on the company's sustainability in a competitive environment